Urgensi Mediasi Terhadap Sengketa Pembagian Harta Bersama - Muhammad Alvin Saputra; Robi’atin A’dawiyah; Tomy Erwansyah; Sri Jati Ratna Sari; Syeh Sarip Hadayatullah (Jurnal USM Law Review)
The primary objective of this study is to highlight the importance of mediation as a more effective alternative method for resolving joint property disputes compared to conventional litigation approaches. Joint property disputes have become an increasingly pressing issue in the realm of family and civil law. These conflicts often arise in the context of divorce, which can cause tension and uncertainty for the parties involved. According to the decision directory of the Supreme Court of Indonesia, there were 2,316 cases of joint property disputes in 2023, indicating that joint property conflicts are widespread. This underscores the urgent need for a more effective alternative solution. The formal legal approach traditionally used in resolving joint property disputes has various limitations. One major constraint is the lack of integration among the various relevant approaches in the mediation process. This study employs three approaches: psychological, economic, and philosophical. Data collection is based on a literature review and utilizes a qualitative descriptive method for data analysis. The study's findings indicate that mediation offers significant advantages over conventional litigation for dispute resolution. The integrated mediation model developed in this study, which combines psychological, economic, and philosophical approaches, is expected to address the weaknesses of existing mediation approaches. With a holistic and adaptive approach to the complexities of joint property disputes, this model has the potential to improve the effectiveness and efficiency of dispute resolution and provide tangible benefits to the involved parties.